Analisis Keselamatan Simpang Jalan Arteri Primer di Kabupaten Sleman Menggunakan Metode TCT - Zulfan Muhammad Ihza; Noor Mahmudah (Department of Civil Engineering, Diponegoro University, 2025)
Traffic safety is an important aspect of a sustainable transportation system. The increase in number of vehicles and high mobility make intersections as the points with the highest risk of accidents. The Special Region of Yogyakarta (DIY), as a province with dynamic tourism and economic activities, has a significant accident rate, with Sleman Regency contributing approximately 34.8% of the total 4,730 accident cases in DIY in 2018. This condition emphasizes the need for a comprehensive traffic safety analysis in this region. This study aims to analyze the safety level of intersections on primary arterial roads in Sleman Regency using the Swedish Traffic Conflict Technique (TCT). The approach was conducted by ranking road sections using the Accident Equivalent Number (AEK) and observing traffic conflicts using the TCT method. The results of the study show that all intersections observed have a high-level of conflict with a Time to Accident (TA) value that is close to or exceeds the critical threshold. Speed has been proven to be the main determinant of increased risk and severity of conflict. Therefore, this study emphasizes the need to calibrate the Swedish TCT threshold based on vehicle type so that the analysis results remain contextual to Indonesian traffic conditions. Technical recommendations focus on speed limits and the implementation of traffic engineering interventions.